Severe persistent allergic asthma - Bodzenta-Łukaszyk, Anna; Skiepko, Roman; Lenczewska, Danuta; Ziętkowski, Ziemowit (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Asthma is a chronic inflammatory disease of the airways. Approximately 60% of asthma cases can be attributed to allergic asthma. The aim of this article is to present the current results concerning the problem of severe persistent allergic asthma, the use of anti-IgE treatment (omalizumab) as well as our own results determining the clinical efficacy and anti-inflammatory activity of Xolair (omalizumab) in patients with severe allergic asthma.